Pembelajaran Adaptif Berbasis Teknologi: Upaya Meningkatkan Keterlibatan dan Hasil Belajar Siswa - Muharleni (Jurnal Ilmu Sosial, Ekonomi dan Pendidikan, 2026)
This study aims to analyze the effectiveness of technology-based adaptive learning in improving student engagement and Indonesian language learning outcomes among elementary school students. The study employed a quantitative approach using a quasi-experimental design with a non-equivalent control group design. The participants consisted of 60 fifth-grade students from an elementary school in Padang, Indonesia, divided into an experimental group and a control group. The experimental group received adaptive learning through a Learning Management System (LMS) equipped with personalized learning features, while the control group received conventional instruction. The learning focus was on reading comprehension and identifying main ideas in nonfiction texts. Data were collected through learning achievement tests, student engagement questionnaires, and classroom observations. Data analysis was conducted using paired sample t-test, independent sample t-test, N-Gain, and Cohen’s d effect size analysis. The findings revealed that technology-based adaptive learning significantly improved students’ learning outcomes compared to conventional learning (p < 0.05), with a large effect size (Cohen’s d = 1.12). In addition, student engagement in the experimental group was higher across cognitive, emotional, and behavioral dimensions. The results indicate that adaptive learning supported by technology creates a more personalized, interactive, and meaningful learning experience. Therefore, technology-based adaptive learning has strong potential to support literacy development and improve the quality of Indonesian language learning in elementary schools in the digital era.